Natural Gas Vehicle (NGV) / Roslan Said and Mohd Adami Muda - Said, Roslan; Muda, Mohd Adami (Faculty of Mechanical Engineering, 2002)
In Malaysia, Natural Gas Vehicle (NGV) is widely used in the commercial vehicles such as taxi. Normally, it can only be found in the urban cities in Malaysia because of inadequate facilities that can support the usage of this technology. This technology is also proven to be friendlier to the environment compared to the petrol engine. Due to that, an alternative fuel that can solve the ecological problems can be obtained from it. However, the knowledge of our people regarding on this system can be considered lagged the other developing countries. Furthermore, it has also been proven that an engine, which is equipped with this system, is less powerful compared to an engine with conventional fuel system. These have encouraged us to choose NGV as the subject of our study in order to acquire in depth understanding of this system. We have already bought all components, which are required to build this system. From there, we started to assemble the whole components before installing the system to an engine. During the assembling and installations process, we had used many types of equipment, which can be found in the workshop. These equipments include the grinding machine, folding machine, drilling machine and welding machine. This project had also required us o build a frame that is used to support the entire system so that the engine can run smoothly. The frame was also built under some considerations in order to avoid any problems that may arise in the future. In our study, we found that the entire system needs a clean air filter to make the engine runs easily. Proper timing is also required to obtain the same result. Finally, the system also needs to be mounted by rubber mounting to reduce vibrations that can cause the components to be defective. Upon completion of the project, the engine is at proper running condition.